Aqueous extracts of Syzygium brazzavillense can inhibit the infection with coxsackievirus B4 in vitro. Issue 7 (3rd March 2019) - Badia‐Boungou, Francis; Sane, Famara; Alidjinou, Enagnon Kazali; Hennebelle, Thierry; Roumy, Vincent; Ngakegni‐Limbili, Adolphe Christian; Nguimbi, Etienne; Moukassa, Donatien; Abena, Ange Antoine; Hober, Didier
Abstract: Traditional practitioners commonly use plant crude extracts to treat various diseases in patients with symptoms that can be seen during enterovirus infections. In this study, the antienteroviral activity of medicinal plants from the Republic of Congo has been evaluated in vitro. Through an ethnopharmacological approach, seven plants grouped into six families were identified. Aqueous and organic extracts of various organs from these plants were prepared. The organic extracts at subcytotoxic concentrations did not inhibit the cytopathic effect (CPE) induced by coxsackievirus (CV)B1‐5, CVA6, poliovirus type 1, and enterovirus 71. The aqueous extract of Syzygium brazzavillense, but not those of other plants, inhibited the CPE induced by CVB3 and CVB4 at 30 µg/mL (CC50 ; 2800 µg/mL, IC50 ; 0.8 µg/mL) and by CVB2 and poliovirus type 1 at higher concentrations. When aqueous extract of this plant was mixed with CVB4, the replication of the virus was inhibited. In conclusion, aqueous extracts of Syzygium brazzavillense can inhibit the infection with CVB4 and other enteroviruses in vitro. The present ethnopharmacological investigation helped to identify a plant with potential properties useful to combat enterovirus infections. Highlights: Very few studies have evaluated the effects of plant extracts against enteroviruses. Through an ethnopharmacological approach, medicinal plants from Republic of Congo have been identified. The aqueous extract of Syzygium brazzavillense, but not those of other plants, inhibited in vitro the cytopâthic effect induced by coxsackievirus B (CVB) 3 and CVB4, CVB2 and poliovirus type 1. The present ethnopharmacological investigation helped to identify a plant with potential properties useful to combat enterovirus infections.